Mapping Sustainability Performance in the Hospitality Industry: A Systematic Literature Review and Future Research Agenda - Ni Luh Putu Mita Miati; Dodik Ariyanto; Anak Agung Gde Putu Widanaputra; I Gusti Ayu Made Asri Dwija Putri (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to identify the main indicators, influencing variables, analytical techniques, and regional trends of sustainability performance in the hospitality industry. Methodology: This study adopts a Systematic Literature Review (SLR) method using the Scopus database as the primary source. Articles were searched through Boolean keyword techniques, screened with PRISMA guidelines, and analysed using descriptive synthesis to map indicators, variables, and methods applied in prior studies. Results/Findings: The review shows that environmental, economic, and social performance remain the most dominant indicators, whereas cultural sustainability is rarely addressed. Green Human Resource Management (GHRM), Corporate Social Responsibility (CSR), and environmental management are the most studied variables. In contrast, green intellectual capital and spiritual capital have not been examined in the hospitality sector, although they show potential relevance. SEM-PLS is identified as the most frequently applied analytical tool, and most studies are concentrated in developing countries. Conclusions: The findings emphasize the need for further research into cultural sustainability and the inclusion of intellectual and spiritual capital in hospitality sustainability practices. The dominance of environmental, economic, and social factors suggests that a broader, more integrated approach is necessary. Limitations: This review is limited to English-language articles indexed in Scopus and excludes non-English or unpublished studies. Contributions: This study makes both theoretical and practical contributions. Theoretically, it expands sustainability research in hospitality by integrating knowledge-based and value-based resources. Practically, it guides hotel managers and policymakers, especially in culturally rich destinations, to incorporate cultural heritage, intellectual capital, and spiritual values into sustainability practices.